Denture wearing is associated with nutritional status among older adults requiring long-term care: A cross-sectional study - Ayami Meguro; Yuki Ohara; Masanori Iwasaki; Ayako Edahiro; Maki Shirobe; Kentaro Igarashi; Keiko Motokawa; Masayasu Ito; Yutaka Watanabe; Yasuhiko Kawai; Hirohiko Hirano (Elsevier, 2022)
Background/purpose: Dentures are important for the reconstruction of occlusal support and masticatory performance for older adults with poor dentition. We aimed to elucidate the oral health factors associated with malnutrition in older adults requiring long-term care, including denture use. Materials and methods: This cross-sectional study included 322 older adults (63 men, 259 women; mean age, 86.6 ± 6.9 years) who required long-term care in rural Japan. The participant's nutritional status was assessed using the Mini Nutritional Assessment-Short Form (MNA®-SF). Oral health was assessed using participant's dentition and oral function. Barthel Index (BI) and medical history were measured for assessing general health status. Multiple logistic regression analyses were performed to determine the oral health factors associated with malnutrition. Results: The proportion of participants with malnutrition was 17.2%. The BI score (odds ratio [OR], 0.95; 95% confidence interval [CI] 0.93-0.98, p<0.001), having <20 teeth and dentures (OR 0.42; 95%CI 0.18-0.99; p = 0.047), and poor lip-closure ability (OR 2.86; 95%CI 1.32-6.20; p = 0.008) were significantly associated with malnutrition. Conclusion: Denture use, lip-closure ability, and activities of daily living were significantly associated with malnutrition in older adults requiring long-term care, suggesting that wearing dentures for tooth loss and maintaining oral function contributes to nutritional status.